A Revised Description of the Larva of Leptocerina pauliani (Ross 1957 (Trichoptera: Leptoceridae), an Endemic Species of La Réunion Island - Forcellini, Maxence (Zootaxa, 2021)
Leptocerina is an endemic Afrotropical genus of Trichoptera, with 19 species documented but only five partially described at the larval stage. The first description of Leptocerina pauliani (Ross 1957) larva by Marlier & Marlier (1982) included very few illustrations, making comparisons with other species challenging. I present a revised description of the L. pauliani larval stage, using specimens collected from the River Marsouins in La Réunion Island. I apply a focus stacking approach for emphasizing coloration patterns and providing a detailed description of larval characters. Criteria for distinguishing L. pauliani from the other species of Leptocerina already described or partially described for the larval stage are discussed.